Estudio De Los Mecanismos De Movimiento Granular En Un Horno Rotatorio (2018)
The main purpose of this work is to identify residence times that occur within the rotary kiln for different raw materials, taking into account operational parameters, the transition that occurs between movements, the characteristics of these raw materials and the initial conditions. of the reactor. This purpose was carried out by means of a simulation of a mathematical model in Matlab, to find residence times taking into account the specification of the borders of each movement and the necessary conditions for the transitions between them to take place, taking into account the operating conditions of the rotary kiln and the physical properties of the raw materials. The comparisons of the theoretical model made with experimental theses were satisfactory so the mathematical model can be used in the analyzed raw materials and is open to other raw materials that we wish to study.